Analysis of Antioxidant Formulations of Watermelon Peel (citrullus lanatus) and Secang Wood (Caesalpinia sappan l.) as Jelly Candy - Fitriani Abubakar, Andi Nur; Zulkarnain, A. Mutiara; Safitri Agustina, Ayu (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Jelly candy made from watermelon rind and sappan wood is a candy with a soft texture that is processed with the addition of gelatin and low-calorie sugar. Based on the literature search that has been carried out. There has been no research regarding the antioxidant activity of jelly candy from watermelon rind and sappan wood. Him this research aims to determine the effect of varying concentrations of watermelon rind and wood extracts sappan in making formulations as jelly candy, the potential of jelly candy as an antioxidant, and to know the SNI 3574.2-2008 standard which includes water content, ash content, reducing sugar content and the condition aroma and taste of jelly candy. The results of the chemical properties test show that the water content in F3 meets SNI namely 19.891995%, and the ash content shows results that meet SNI, namely at F1 0.028%, F2 0.02905% and F3 0.02985%. Meanwhile, the reduced sugar content also shows results that meet SNI, namely F1 0.00219%, F2 0.00144% and F3 0.00048%. The organoleptic test results on the color indicator are 6.72 (somewhat like), the indicator of the aroma is 6.43 (somewhat like) and the taste indicator is 6.54 (somewhat like) and has met SNI with the condition normal. The results of the antioxidant activity test are in the medium category with an inhibition value of 36%.